The Trump Doctrine and the Emerging International System - Renshon, Stanley A.; Suedfeld, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
President Donald J. Trump$1 (Bs (3z(BAmerica First(3y (Boutlook has inspired both enthusiasm and condemnation among different segments of the American population. This book examines the meaning and implications of that perspective, and how the Trump Administration has implemented it$1 (Bor failed to do so. Contributors, subject-matter experts with diverse points of view, place the Trump Doctrine within the succession of presidential foreign policy themes, and provide a case-by-case analysis of how it has been applied in specific regions and countries around the world. The book$1 (Bs aim is to provide a fair and balanced assessment, relatively rare in this period of intense partisanship and impending national election. Stanley Renshon is Professor of Political Science at the City University of New York, Herbert H. Lehman College and the Graduate School and University Center, USA, and a certified psychoanalyst. Peter Suedfeld is Dean Emeritus of Graduate Studies and Professor Emeritus of Psychology at the University of British Columbia, Canada.s
1. The Trump Doctrine and Conservative American Nationalism -- 2. National Interests and the Trump Doctrine: The Meaning of "American First" -- 3. Trump and America's Foreign Policy -- 4. The Trump Doctrine and the Institutions of the Liberal International Order -- 5. Foreign Policy Decision Making in the Trump Administration -- 6. Deterrence, Compellence, and the Containment in the Trump Foreign Policy: Comparing Present and Past Strategies of American Leadership -- 7. The New Normal?: Public Opinion, Partisanship, and the Trump Doctrine -- 8. The End of the Affair: U.S.-China Relations under Trump -- 9. "Beyond Hyperbole: The Real Meaning of the Trump-Kim Dialogue -- 10. The Trump Doctrine in the Middle East -- 11. Trump, Israel, and the Shifting Pattern of Support for a Traditional Ally -- 12. The Trump. Obama and Bush Doctrines: A Comparative Analysis -- 13. American Nationalism and the Future of the Trump Doctrine. .
Keywords: United States$1 (BPolitics and government.s; International relations; Legislative bodies; Security, International; Diplomacy; US Politics; Foreign Policy; Legislative and Executive Politics; International Security Studies; Diplomacy